An Analysis of code-switching in Hitz FM instagram comments - Munirah ‘Izzati Ismail,; Nor Eleyana Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The phenomenon of code-switching nowadays used by the multilingual society and online community such as in Malaysia to communicate is often encountered on various social media platforms,including Instagram. Haryanto and Mahendra (2021) posited that code-switching is frequently found on Instagram and usually used by bilingual communities to write captions for photos or videos, and in their comments. However, the research on analysing code-switching on Instagram in Malaysian context is still understudied. Thus, this study aimed to examine the types of Malay-English code-switching expression on Hitz FM Instagram comment, and the reasons for code-switching in social networking websites by employing the framework by Poplack (1980) and Malik (1994) respectively. A thematic analysis was used to classify a one-year data consisting of f 323 Instagram comments into types and reasons for code-switching. The findings revealed the most occured type was intra-sentential (75.85%) followed by tag-switching (17.03%) and inter-sentential (7.12%). Whereas, out of the 10 reasons by Malik (1994), only 8 were found with the most reason was due to lack of competence (41.18%). Therefore, the findings suggest that social media users in a multilingual society frequently code-switch for various reasons when communicating on Instagram. It is hoped that the findings from this study will contribute more insights into the field of linguistics, and benefit future research.